Diversity and Distribution of Polyporales in Peninsular Malaysia (Kepelbagaian dan Taburan Polyporales di Semenanjung Malaysia) - Mohammad Hasnul, Bolhassan; Noorlidah, Abdullah; Vlkineswary, Sabarantnam; Hattori, Tsufomu; Sumaiyah, Abdullah; Noraswati, Mohd Noor Rashid; Md. Yusoff, Musa (Universiti Kebangsaan Malaysia, 2012)
Macrojungi ofthe order Polyporales are among the most important wood decomposers and caused economic losses by decaying the wood in standing trees, logs and in sawn timber. Diversity and distribution ofPolyporales in Peninsular Malaysia was investigated by collecting basitliocarps from trunks, branches, exposed roots and soilfrom six states (lohar, Kedah, Kelantan, Negeri Sembilan, Pahang and Selangor) in Peninsular Malaysia and Federal Territory Kuala Lumpur. This study showed that the diversity ofPolyporales were less diverse than previously reported. The study identified 60 species from five families; Fomitopsidaceae, Ganodermataceae, Meruliaceae. Meripiiaceae. and Polyporaceae. The common species of Polyporales collected were Fomitopsis feei. Amauroderma subrugosum. Ganoderma australe, Earliel1a scabrosa, Lentinus squarrosulus, Microporus xanthopus. Pycnoporus sanguineus and Trametes menziesii.